Spatiotemporal distribution and evolution pattern of Chinese Go League clubs in 20 years of professionalism - Kunlun, Chen; Xiaoqiong, Liu; Xu, Zhang; Lei, Ding (Frontiers in Sports and Active Living, 2023)
Over the course of 20 years, from 1999 to 2018, the Chinese Go League has gradually developed and flourished, becoming a significant part of urban sports culture. Using mathematical statistics, spatiotemporal trajectory, and geospatial analysis, this research investigates the spatiotemporal distribution pattern and diffusive evolution characteristics of Chinese Go League clubs from the perspective of sports geography. The results of this study show that the following: (1) Over the past 20 years, the number of Chinese Go League clubs has increased in a “stepped” pattern, and there is still plenty of room for expansion. (2) Chinese Go League clubs are primarily located in municipalities directly under the central government and provincial capital cities (accounting for 82.6% of the total), with the Bohai Rim, Yangtze River Delta, and Southwest region of China forming a spatial pattern. (3) Host cities of Chinese Go League clubs are generally discrete, with clustering and random distribution occurring only seldom. The spatial distribution also tends to favor southern cities. (4) Chinese Go League clubs frequently change their names and host cities, and they have a variety of links with those cities, which primarily includes urban stability, urban transition, and urban fluctuation. In future, the professionalization and sustainable development of Chinese Go industry can be enhanced by the marketability of Chinese Go clubs, developing new markets for Chinese Go, and building a healthy development model with multiple linkages of Chinese Go clubs, sponsors, and host cities.